Payung Geulis (Tasikmalaya City) : Between Existence, Regeneration and Local Wisdom - Danial Kusumah; Dede Aji Mardani; Rani Nurnawati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
As a city of Islamic students, Tasikmalaya City is also known as the pioneer city of Geulis umbrellas, whichhas existed since the Dutch era. The purpose of this research is toanalyse the dimensions of development stagnation and repositioning of Geulis umbrella craftsmen. Geulis umbrella craftsmen. The method used is a field study withqualitative socio-anthropological model, interviewing 13 raw material craftsmen,painters, owners, frame and ball craftsmen. The results showedthat the biggest problem faced by the craftsmen is the problem of regeneration.regeneration, craftsmen, lack of access to national and international exhibitions, coaching, regulatory support, funding assistance, access to technology for making balls and frames. While for marketing with traditional methods is higher than with online method, because the market share is clear-stable-consistent, but with different prices. different prices. Raw materials are abundant, while labour labour is still dependent on the older generation over 50 years old, as well as the the lack of technological tools in making balls, the frame is still manual. One of one form of commitment-motivation of craftsmen to local wisdom products is the love of producing Geulis umbrellas that have been passed down from generation to generation to keep producing Geulis umbrellas that have been passed down from generation to generation, even though there are many more practical and functional umbrellas, umbrellas that are more practical and functional.